Refining the Translation of Accurate Perceptions into an Accurate Prescription: A Case of Beaucarnea recurvata - Anderson, David John (Homœopathic Links, 2017)
The author describes the challenge the homeopath has in making an accurate translation of a well-perceived and well-taken case into an accurate prescription. Using a case spanning 25 years of mostly non-helpful prescriptions, he describes how utilizing the seven parameters of Jan Scholten's analytical framework of perceiving and conceptualizing human suffering and the Plant kingdom guided him to an accurate and highly effective remedy.
Keywords: Beaucarnea recurvata; Asparagales; Jan Scholten; Hahnemann